The Policies of the European Union from an East- Central European Perspective Tax Policy - Kačaljak, Matej (The Policies of the European Union from a Central European Perspective, 2022)
This chapter concerns the reflections of selected Central European Member States on the Tax Policy of theEuropean Union. The legislation and case law of courts in these states constantly reflect upon the CJEU case law and initiatives of other European Union institutions on one side, but also upon the legislative and juridical movements in each other. Three particular areas are discussed where this recurrent process is illustrated, namely the concept of General Anti-Abuse Rules (GAARs), the issue of VAT fraud and particularly of thirdparty liability and, finally, the area of special (sectoral) levies. The GAARs eventually became harmonized through the ATAD directive, but up to that moment, very different approaches could be observed between the Central European Member States, with some being early adopters even before accession to the European Union either through legislative enactment (Hungary) or through development of judicial doctrines (Czech Republic) but also with others that have enacted their GAARs only relatively recently (Slovak Republic, Poland). The issue of VAT fraud and third-party liability shows that referrals from Central European Member States (especially Hungary) have been a strong driver of the CJEU case law in this area. Finally, the special levies enacted by Central European Member States and CJEU proceedings they have triggered have provided very useful insight to testing the compatibility of sectoral levies with European Union law but also to the recent discussions on the digital services taxes. Keywords: corporate income tax, general anti-abuse rule (GAAR), VAT fraud, third-party liability, equalization levy, special review